Plant protein-polysaccharide complex particle stabilized pickering emulsion and use thereof
Patent Information
- Application Number
- CN202611117096.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-30
AI Technical Summary
虽然蛋白质-多糖复合颗粒因同时具有良好的表面活性、较强的空间稳定能力和优异的氧化稳定性已有相关研究,但基于改性藜麦蛋白-沙蒿胶复合颗粒的Pickering乳液的研究与应用未见报道
1.本发明通过500W超声波改性处理,显著改善了藜麦蛋白的理化、结构和功能特性。改性后藜麦蛋白的粒径和浊度显著降低,zeta电位绝对值、表面疏水性和活性巯基含量显著升高,溶解度由7.17%提高至69.23%,乳化活性指数由19.96m2/g提高至35.77m2/g,乳化稳定性指数由44.85min提高至97.43min,激光共聚焦图像显示蛋白分布最均匀致密,有效解决了天然藜麦蛋白溶解性和乳化性差的技术问题。
Smart Images

Figure CN122997328A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of food processing technology, specifically relating to a plant protein-polysaccharide composite particle stabilized Pickering emulsion and its application. Background Technology
[0002] Pickering emulsions are emulsions stabilized by replacing surfactants with solid particles, and they have significant application potential in areas such as fat substitutes, composite material preparation, drug delivery carriers, and the delivery and encapsulation of bioactive ingredients. Unlike traditional emulsions, picking emulsions rely on irreversible interfacial adsorption of solid particles, exhibiting better anti-agglomeration stability. In recent years, most studies have used single inorganic particles, organic polymers, and food-grade particles as emulsifiers to construct picking emulsions.
[0003] However, single solid particles cannot achieve synergistic effects, resulting in low emulsification efficiency and limited emulsion stability, thus restricting their application in the food industry. Therefore, the development of food-grade composite particle emulsifiers has gradually become a research hotspot. Modified quinoa protein is rich in essential amino acids such as lysine, tryptophan, and cysteine, offering high nutritional value and good solubility and emulsifying properties. Artemisia gum possesses excellent thermal stability, rheological properties, and water retention. Although protein-polysaccharide composite particles have been studied due to their good surface activity, strong steric stability, and excellent oxidative stability, research and applications of Pickering emulsions based on modified quinoa protein-Artemisia gum composite particles have not been reported.
[0004] In view of this, the present invention studies the effects of ultrasound on the physicochemical, structural and functional properties of quinoa protein, determines the optimal modified ultrasound power of quinoa protein, and on this basis constructs a stable Pickering emulsion of modified quinoa protein and Artemisia argyi gum composite particles, and applies it as a fat substitute in low-fat emulsified intestines. Summary of the Invention
[0005] The purpose of this section is to outline some aspects of embodiments of the present invention and to briefly describe some preferred embodiments. Simplifications or omissions may be made in this section, as well as in the abstract and title of this application, to avoid obscuring the purpose of these documents; however, such simplifications or omissions should not be construed as limiting the scope of the invention.
[0006] In view of the problems existing in the above and / or prior art, the present invention is proposed.
[0007] One object of the present invention is to provide a modified quinoa protein-Artemisia gum composite particle, its Pickering emulsion, and its application.
[0008] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a Pickering emulsion stabilized by plant protein-polysaccharide composite particles, characterized in that the Pickering emulsion uses plant protein-polysaccharide composite particles as emulsifier, plant oil as oil phase, and water as water phase; the plant protein-polysaccharide composite particles are composed of ultrasonically modified plant protein and plant gum.
[0009] Preferably, the modified plant protein is modified quinoa protein; and the plant gum is Artemisia argyi gum.
[0010] Preferably, the mass ratio of the modified quinoa protein to Artemisia argyi gum is 1:4 to 5:1.
[0011] Preferably, the mass ratio of the modified quinoa protein to Artemisia argyi gum is 1:2 to 2:1.
[0012] Preferably, the modified quinoa protein is obtained by treating natural quinoa protein with low-frequency, high-intensity ultrasound.
[0013] Preferably, the ultrasonic power of the low-frequency high-intensity ultrasonic treatment is 200W-600W.
[0014] Preferably, in the Pickering emulsion, the mass concentration of the composite particles is 0.5%-1.5%; and the volume fraction of the oil phase is 60%-75%.
[0015] Preferably, the mass concentration of the composite particles is 1.5%, and the volume fraction of the oil phase is 70%.
[0016] Another object of the present invention is to provide a low-fat emulsified sausage, which is prepared from the following raw materials in parts by weight: 200 parts of pig back ribs, 0-30 parts of fat, 10-40 parts of Pickering emulsion as described in any one of claims 1-8, 40 parts of ice water, 4 parts of salt, 0.4 parts of white pepper powder, and 0.6 parts of sodium polyphosphate.
[0017] Preferably, the Pickering emulsion replaces 50% of the fat.
[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention significantly improves the physicochemical, structural, and functional properties of quinoa protein through 500W ultrasonic modification. After modification, the particle size and turbidity of the quinoa protein are significantly reduced, while the absolute value of the zeta potential, surface hydrophobicity, and active thiol content are significantly increased. Solubility increases from 7.17% to 69.23%, and the emulsifying activity index increases from 19.96 μm. 2 / g increased to 35.77m 2 / g, the emulsification stability index increased from 44.85min to 97.43min, and the laser confocal image showed that the protein distribution was the most uniform and dense, effectively solving the technical problem of poor solubility and emulsification of natural quinoa protein.
[0019] 2. This invention combines ultrasonically modified quinoa protein with Artemisia annua gum to prepare composite particles with an MQP:ASKG ratio of 1:1. The particles have a diameter of 159.23 nm, an absolute zeta potential of 31.53 mV, and a three-phase contact angle of 109.71 ± 0.70°, exhibiting good wettability and interfacial adsorption capacity. When c = 1.5%, At 70%, the Pickering emulsion exhibited the smallest droplet size (11.94 μm), the highest gel strength (28.11 g), the highest centrifugal stability (98.14%), and the best lutein retention rate (86.86%), demonstrating excellent stability.
[0020] 3. This invention applies the aforementioned Pickering emulsion as a fat substitute to low-fat emulsified sausages, significantly improving the quality characteristics of the low-fat emulsified sausages without reducing textural properties or sensory acceptability. When 50% of the fat is replaced, the gel strength of the low-fat emulsified sausage reaches its peak (1604.46 g), which is 10.6% higher than the full-fat control group, effectively solving the technical problem of quality deterioration of emulsified sausages caused by directly reducing fat content. Attached Figure Description
[0021] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein: Figure 1 This illustrates the effect of different ultrasonic powers on the turbidity of quinoa protein in Example 1 of the present invention.
[0022] Figure 2 This illustrates the effect of different ultrasonic powers on the particle size distribution (A) and average particle size (B) of quinoa protein in Example 1 of the present invention.
[0023] Figure 3 This illustrates the effect of different ultrasonic powers on the zeta potential of quinoa protein in Example 1 of the present invention.
[0024] Figure 4 This illustrates the effect of different ultrasonic powers on the SDS-PAGE spectra of quinoa protein in Example 1 of this invention.
[0025] Figure 5 This illustrates the effect of different ultrasonic powers on the surface hydrophobicity of quinoa protein in Example 1 of the present invention.
[0026] Figure 6 This illustrates the effect of different ultrasonic powers on laser confocal microscopy images of quinoa protein in Example 1 of the present invention.
[0027] Figure 7 This illustrates the effect of different ultrasonic powers on the solubility of quinoa protein in Example 1 of the present invention.
[0028] Figure 8 This illustrates the effect of different ultrasonic powers on the emulsification properties of quinoa protein in Example 1 of the present invention.
[0029] Figure 9 The average particle size (A) and zeta potential (B) of the MQP-ASKG composite particles with different proportions in Example 2 of the present invention are shown.
[0030] Figure 10 This illustrates the effect of particle concentration and oil phase volume fraction on Pickering emulsion gel formation in Example 2 of the present invention.
[0031] Figure 11 This illustrates the effect of particle concentration and oil phase volume fraction on the gel strength of Pickering emulsion in Example 2 of the present invention.
[0032] Figure 12 This describes the effect of particle concentration and oil phase volume fraction on the stability of Pickering emulsion lutein in Example 2 of the present invention.
[0033] Figure 13 This invention illustrates the effect of Pickering emulsion replacing different proportions of fat on the yield of low-fat emulsified sausage during cooking in Example 3.
[0034] Figure 14 This invention illustrates the effect of Pickering emulsion replacing different proportions of fat on the water retention of low-fat emulsified intestines in Example 3.
[0035] Figure 15 This invention illustrates the effect of Pickering emulsion replacing different proportions of fat on the strength of low-fat emulsified enteric gel in Example 3.
[0036] Figure 16 This invention describes the effect of Pickering emulsion replacing different proportions of fat on the relaxation time (A), T2 relaxation time (B), and P2 peak area ratio (C) of low-fat emulsified intestinal LF-NMR in Example 3 of this invention.
[0037] Figure 17 This study describes the effect of Pickering emulsion replacing different proportions of fat on the sensory evaluation of low-fat emulsified intestines in Example 3 of the present invention. Detailed Implementation
[0038] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.
[0039] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0040] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.
[0041] Unless otherwise specified, all raw materials used in this invention are commercially available in the field. Quinoa was purchased from Shandong Laoxiang Ecological Agriculture Co., Ltd., and the chemical reagents such as sodium hydroxide, copper sulfate, potassium sodium tartrate, potassium iodide, potassium dihydrogen phosphate, disodium hydrogen phosphate, and bromophenol blue were all analytical grade and purchased from Tianjin Kemeio Chemical Reagent Co., Ltd. Sodium dodecyl sulfate was purchased from Guangdong Xilong Science Co., Ltd., crystalline bovine serum albumin was purchased from Zhengzhou Penny Chemical Reagent Factory, and Nile blue was purchased from Sigma-Aldrich, Inc.
[0042] The following methods are used to detect each indicator in this invention: 1. Turbidity: The quinoa protein suspension was diluted to 2 mg / mL using 0.05 M phosphate buffer, and the absorbance of the sample was measured at 600 nm using a UV-Vis spectrophotometer.
[0043] 2. Particle size and zeta potential: Particle size was measured using a laser nanoparticle size analyzer. The sample was diluted to 1 mg / mL with phosphate buffer (0.05 M) and measured and analyzed at 25 °C.
[0044] 3. SDS-PAGE gel electrophoresis: Mix 30 μL of quinoa protein suspension (3 mg / mL) with 10 μL of 4× buffer and incubate at 100℃ for 5 min. Add 15 μL of sample and marker to an SDS-PAGE gel (4% stacking gel, 20% separating gel) and perform electrophoresis at 80V and 120V respectively. Stain the gel with R-250 Coomassie Brilliant Blue solution for 60 min, fix in fixative for 10 min, and destain in destaining solution for 8 h until the bands are clear.
[0045] 4. Surface hydrophobicity: Determined using the bromophenol blue binding method. 2 mL of quinoa protein suspension (5 mg / mL) and 400 μL of bromophenol blue solution (1 mg / mL) were mixed thoroughly by shaking at room temperature for 10 min. The mixture was then centrifuged at 6000 × g for 15 min. The supernatant was diluted 10-fold with phosphate buffer (0.05 M), and the absorbance was measured at 595 nm. The formula for calculating surface hydrophobicity is as follows: Bromophenol blue binding capacity (μg) = 400 × (OD) 空白 -OD 样品 ) / OD 空白 5. Active thiol content: Mix 1.5 mL of quinoa protein suspension (5 mg / mL) and 10 mL of Tris-glycine buffer (pH=8) thoroughly, then add 50 μL of Lellman's reagent and incubate at 25°C for 1 h. Centrifuge the sample (12000 × g, 10 min), collect the supernatant, and measure the absorbance at 412 nm. The active thiol content is calculated using the following formula: Active thiol content (μmol / g) = (73.53 × A) 412 ) / C In the formula, 73.53 = 10 6 / 13600, where 13600 is the molar extinction coefficient; C is the sample concentration, mg / mL.
[0046] 6. Intrinsic fluorescence spectrum: The intrinsic fluorescence intensity of the quinoa protein suspension (0.1 mg / mL) was measured using a fluorescence spectrophotometer. The measurement parameters were: excitation wavelength 280 nm, emission wavelength 300–450 nm.
[0047] 7. UV-Vis Absorption Spectroscopy: The UV absorption spectrum of quinoa protein suspension (0.5 mg / mL) was measured using a UV spectrophotometer in the wavelength range of 200-400 nm. The scan rate was set to 50 nm / min and the resolution to 0.5 nm. The sample was scanned three times, and the average value was calculated. The UV second-guide spectrum was analyzed and calculated using Origin 2024 software.
[0048] 8. Fourier Transform Infrared Spectroscopy: Freeze-dried quinoa protein powder and potassium bromide were mixed at a 1:100 ratio and compressed into tablets. Near-infrared spectra of the samples in the 400-4000 / cm⁻¹ wavelength range were acquired using a TENSOR27 Fourier Transform Infrared Spectrometer at a resolution of 4 cm⁻¹. Simultaneously, potassium bromide was used as a background, and the samples were scanned 32 times and overlaid. The data were deconvolved using Omnic 8.0 and Peakfit 4.12 software to analyze changes in the secondary structure of quinoa protein.
[0049] 9. Laser confocal microscopy: The microstructure of quinoa protein in the suspension was observed using a laser confocal scanning microscope. After uniformly mixing 20 μL of Nile blue (1 mg / mL) and 1 mL of quinoa protein suspension (10 mg / mL), 10 μL was dropped onto a glass slide, covered with a coverslip, and the microstructure of the sample was observed at an excitation wavelength of 633 nm and a magnification of 5×.
[0050] 10. Solubility: The quinoa protein suspension was diluted to 5 mg / mL with phosphate buffer (0.05 M), and the supernatant was collected after centrifugation at 4 °C and 9000 × g for 15 min. The protein concentration in the supernatant and the protein solution before centrifugation was determined using the biuret method. Solubility was calculated using the following formula: Solubility (%) = (Supernatant protein concentration / Total protein concentration) × 100 11. Static rheological properties: 3 mL of quinoa protein suspension (30 mg / mL) was placed on a P60 (60 mm diameter, 1 mm gap) circular aluminum plate. Using a MARS dynamic rheometer, the properties of the sample were measured at 25 °C and a fixed frequency of 0.1 Hz within the range of 0.01–1000 s⁻¹. -1 Apparent viscosity and shear stress at shear rate.
[0051] 12. Emulsifying Performance Determination: Quinoa protein suspension and sunflower seed oil were mixed evenly at a volume ratio of 3:1, and then homogenized at 12000 r / min for 2 min using a high-speed disperser to obtain an emulsion. Immediately afterwards, 50 μL of the emulsion was mixed evenly with 5 mL of SDS (0.1 g / 100 mL), and the absorbance value (500 nm) A0 was measured. After the emulsion stood for 30 min, the absorbance value A30 was measured. Emulsifying activity (EA) and emulsifying stability (ES) were calculated using the following formulas: In the formula, T = 2.303; DF is the dilution factor; C is the protein concentration before emulsion formation, in g / mL; =0.01 represents the optical path length; θ=0.25 represents the volume fraction of the oil phase in the emulsion.
[0052] Example 1 This embodiment provides a method for preparing modified quinoa protein, comprising the following steps: (1) Quinoa protein extraction: Plump, dried quinoa grains were pulverized and passed through a 100-mesh sieve to collect the powder. The quinoa powder was mixed with distilled water at a ratio of 1:35 (g / mL), and the pH was adjusted to 10.0 with NaOH (1 mol / L) solution. Quinoa protein was extracted using an ultrasonic cleaner at 35℃ and 400W, with continuous stirring for 2 hours. After centrifugation (8000×g, 10 min), the supernatant was collected, and the pH was adjusted to 4.5. After standing for 0.5 hours, the precipitate was collected; the precipitate was quinoa protein. The obtained quinoa protein was washed three times by centrifugation with distilled water (7000×g, 15 min), the pH was adjusted to 7.0, and after freeze-drying, it was stored in a sealed container at 4℃.
[0053] (2) Ultrasonic treatment: The quinoa protein powder obtained in step (1) was dispersed in deionized water to prepare a protein suspension with a concentration of 20 mg / mL (pH=7.0). The suspension was stirred at room temperature (25℃) for 30 min until fully mixed to obtain the quinoa protein suspension. The quinoa protein suspension was treated with an ultrasonic power of 500W for 15 min (pulse duration of 3s, interval of 2s). The entire treatment process was carried out using a circulating ice water system to avoid overheating and denaturation of the quinoa protein.
[0054] Comparative Example 1-1 The difference between this comparative example and Example 1 is that the ultrasonic power in step (2) is 0W, while the other process parameters and operating conditions are the same as in Example 1.
[0055] Comparative Examples 1-2 The difference between this comparative example and Example 1 is that the ultrasonic power in step (2) is 200W, while the other process parameters and operating conditions are the same as in Example 1.
[0056] Comparative Examples 1-3 The difference between this comparative example and Example 1 is that the ultrasonic power in step (2) is 300W, while the other process parameters and operating conditions are the same as in Example 1.
[0057] Comparative Examples 1-4 The difference between this comparative example and Example 1 is that the ultrasonic power in step (2) is 400W, while the other process parameters and operating conditions are the same as in Example 1.
[0058] Comparative Examples 1-5 The difference between this comparative example and Example 1 is that the ultrasonic power in step (2) is 600W, while the other process parameters and operating conditions are the same as in Example 1.
[0059] Example 1 and Comparative Examples 1-5 were characterized according to the aforementioned detection method.
[0060] Regarding turbidity, by Figure 1 It can be seen that the turbidity value of quinoa protein in Comparative Example 1 was the highest (0.39). As the ultrasonic power increased from 200W to 600W, the turbidity of quinoa protein showed a trend of first significantly decreasing and then slightly increasing. When the ultrasonic power was 500W, the turbidity reached the minimum value (0.22).
[0061] Regarding particle size and zeta potential, Figure 2 It can be seen that the particle size distribution of quinoa protein before and after ultrasonic treatment both exhibit a single-peak distribution. Compared with the peak value of untreated quinoa protein (615 nm), with the increase of ultrasonic power, the peak position of quinoa protein shifts significantly towards a smaller particle size distribution region. As the ultrasonic power increases from 0 W to 500 W, the average particle size of quinoa protein decreases from 773.67 nm to 263.80 nm. When the ultrasonic power is further increased to 600 W, the average particle size of quinoa protein significantly increases to 318.10 nm, and the peak value of the particle size distribution curve shifts towards a larger particle size direction. Figure 3 As shown, the absolute value of the zeta potential of untreated quinoa protein (17.51 mV) is relatively small. With the increase of ultrasonic power, the absolute value of the zeta potential of quinoa protein gradually increases, reaching a peak value of 42.82 mV at 500 W.
[0062] Figure 4 This study shows the effect of different ultrasonic powers on the SDS-PAGE patterns of quinoa protein. All quinoa protein samples exhibited similar bands, mainly composed of 7S globulin at 60 kDa, acidic 11S (AS) globulin at 33-36 kDa, and basic 11S (BS) globulin at 20-22 kDa. Compared with untreated quinoa protein, the 7S and 11S globulin bands of ultrasonically treated quinoa protein were wider and darker.
[0063] Figure 5 The study showed the effect of different ultrasonic power treatments on the surface hydrophobicity of quinoa protein. When the ultrasonic power increased from 0W to 600W, the surface hydrophobicity of quinoa protein first increased and then decreased, reaching a maximum value (35.89μg) at 500W, which was 222% higher than that of untreated quinoa protein (11.14μg). When the ultrasonic power increased to 600W, the surface hydrophobicity of quinoa protein decreased significantly.
[0064] Figure 6Laser confocal microscopy images of quinoa protein under different ultrasonic powers are shown. Untreated quinoa protein exhibits large, irregular particle morphology and uneven distribution. As the ultrasonic power (200-600W) increases, the laser confocal images show that the quinoa protein is more uniformly distributed, large aggregates disintegrate, and the particle size gradually decreases. Furthermore, at an ultrasonic power of 500W, the quinoa protein images show the most uniform and dense protein distribution; however, at 600W, some small aggregates are observed.
[0065] like Figure 7 As shown, the solubility of untreated quinoa protein was low (7.17%), and the solubility of quinoa protein increased significantly with increasing ultrasonic treatment power (200-500W). P<0.05 When the ultrasonic power reaches 500W, the solubility is the highest (69.23%). However, when the ultrasonic power is further increased to 600W, the solubility of quinoa protein decreases significantly.
[0066] Figure 8 The effect of different ultrasonic powers on the emulsification properties of quinoa protein was shown. Ultrasonic treatment significantly increased the EAI and ESI of quinoa protein (P<0.05). With increasing ultrasonic power (0-600W), compared to untreated quinoa protein (19.96m³), the EAI and ESI of quinoa protein decreased. 2 Compared to (g, 44.85 min), EAI increased by 30%, 42%, 60%, 79%, and 61%, respectively, while ESI increased by 17%, 18%, 68%, 117%, and 106%, respectively, all reaching their maximum values (35.77 m) at 500 W. 2 / g, 97.43min). However, when the ultrasonic power was further increased to 600W, the emulsifying properties decreased significantly (P<0.05).
[0067] Based on the above results, in Example 1, the 500W treatment group showed significantly higher solubility and emulsification performance than the untreated group and other power groups (P<0.05), with the lowest particle size and the most uniform and dense microstructure. Low power (200W, 300W, 400W) resulted in insufficient modification, while excessively high power (600W) led to protein re-aggregation and functional degradation. Therefore, 500W was determined to be the optimal ultrasonic modification power for subsequent examples.
[0068] Example 2 This embodiment provides a modified quinoa protein-Artemisia gum composite particle and a Pickering emulsion stabilized therefrom.
[0069] (1) Preparation of MQP-ASKG composite particles: The freeze-dried modified quinoa protein was dispersed in deionized water to prepare a protein solution (3.0%, w / v, pH=7), and stirred at room temperature for 20 min until fully dissolved. The quinoa protein solution was then incubated at 4°C for 12 h to ensure complete hydration. Finally, the quinoa protein solution was centrifuged at 6000 rpm for 15 min to remove insoluble substances. Artemisia argyi (1.0%, w / v) was added to deionized water and magnetically stirred overnight at 500 rpm. The Artemisia argyi solution was then filtered through a 0.45 μm pore size filter membrane. The quinoa protein solution and Artemisia argyi solution were stirred at 500 rpm for 2 h at a 1:1 ratio until a white suspension was formed, thus preparing MQP-ASKG composite particles. These particles were then freeze-dried under vacuum and sealed for subsequent emulsion preparation.
[0070] (2) Preparation of MQP-ASKGPickering emulsion: Freeze-dried MQP-ASKG composite particles were dispersed in deionized water and stirred for 2 hours. The mixture was then allowed to stand at room temperature for 12 hours to fully hydrate, thus preparing an MQP-ASKG suspension. Using the MQP-ASKG suspension as the aqueous phase and sunflower seed oil as the oil phase, the mixture was sheared at 12000 rpm for 2 minutes to obtain the oil phase volume fraction. Pickering emulsion with a concentration of 70% and a particle concentration of c=1.5%.
[0071] Comparative Example 2-1 The difference between this comparative example and Example 2 is that the mass ratio of MQP to ASKG in step (1) is 2:1, while the other process parameters and operating conditions are the same as in Example 2.
[0072] Comparative Example 2-2 The difference between this comparative example and Example 2 is that the mass ratio of MQP to ASKG in step (1) is 3:1, while the other process parameters and operating conditions are the same as in Example 2.
[0073] Comparative Examples 2-3 The difference between this comparative example and Example 2 is that the mass ratio of MQP to ASKG in step (1) is 4:1, while the other process parameters and operating conditions are the same as in Example 2.
[0074] Comparative Examples 2-4 The difference between this comparative example and Example 2 is that the mass ratio of MQP to ASKG in step (1) is 5:1, while the other process parameters and operating conditions are the same as in Example 2.
[0075] Comparative Examples 2-5 The difference between this comparative example and Example 2 is that the mass ratio of MQP to ASKG in step (1) is 1:2, while the other process parameters and operating conditions are the same as in Example 2.
[0076] Comparative Examples 2-6 The difference between this comparative example and Example 2 is that the mass ratio of MQP to ASKG in step (1) is 1:3, while the other process parameters and operating conditions are the same as in Example 2.
[0077] Comparative Examples 2-7 The difference between this comparative example and Example 2 is that the mass ratio of MQP to ASKG in step (1) is 1:4, while the other process parameters and operating conditions are the same as in Example 2.
[0078] Comparative Examples 2-8 The difference between this comparative example and Example 2 is that the particle concentration c in step (2) is 0.5%, while the other process parameters and operating conditions are the same as in Example 2.
[0079] Comparative Examples 2-9 The difference between this comparative example and Example 2 is that the particle concentration c in step (2) is 1.0%, while the other process parameters and operating conditions are the same as in Example 2.
[0080] Comparative Examples 2-10 The difference between this comparative example and Example 2 is that the oil phase volume fraction mentioned in step (2) is different. =65%, and the remaining process parameters and operating conditions are the same as in Example 2.
[0081] Comparative Example 2-11 The difference between this comparative example and Example 2 is that the oil phase volume fraction mentioned in step (2) is different. =75%, and the remaining process parameters and operating conditions are the same as in Example 2.
[0082] Example 2 and Comparative Examples 2-1 to 2-11 were characterized according to the aforementioned detection method.
[0083] like Figure 9 As shown in Figure A, with the increase of the MQP:ASKG ratio (increase in MQP concentration), the average particle size of the composite particles shows an increasing trend, from 159.23 nm (1:1) to 241.83 nm (5:1). With the increase of the MQP:ASKG ratio (increase in ASKG concentration), the average particle size of the composite particles gradually decreases, from 235.01 nm (1:4) to 160.47 nm (1:2). like Figure 9As shown in Figure B, all samples carried a negative charge. The composite particles exhibited the highest absolute zeta potential (31.53 mV) when the MQP:ASKG ratio was 1:1. The absolute zeta potential decreased with increasing MQP concentration. The results also indicated that the composite particles prepared at ratios of 1:1, 2:1, 1:3, and 1:2 had smaller particle sizes.
[0084] Figure 10 The particle concentration was displayed. c ) and oil phase volume fraction ( The effect of oil phase concentration (80%) on Pickering emulsion gel formation was investigated. With samples upright, regardless of particle concentration (0.5-1.5%), emulsions with an oil phase volume fraction of 80% exhibited significant phase separation, while emulsions with other oil phase volume fractions (60-75%) did not show stratification. This indicates that excessively high oil phase volume fractions (80%) are detrimental to Pickering emulsion formation. With samples inverted, when the oil phase volume fraction was 60-65%, [the following text appears to be incomplete and requires further context: "in..."] c=0.5% The emulsion in the bottle is relatively fluid at this time. c=1.0% The emulsion's fluidity decreases at this time. c=1.5% The emulsion remained largely unchanged, indicating that a stable Pickering emulsion gradually formed as the particle concentration increased. When the particle concentration was 0.5%, the oil phase volume fraction increased from 60% to 75%, and the appearance of the emulsion changed significantly. =60-65% The emulsion has low viscosity and high fluidity. =70% The stability of the emulsion is improved. =75% The emulsions formed emulsion gels, indicating that increasing the oil phase volume fraction favored emulsion gel formation. When the particle concentration was 1.0%, the emulsion tended to form an emulsion gel, and this process was even more pronounced when the particle concentration was further increased to 1.5%. Furthermore, the emulsion with a 75% oil phase volume fraction completely gelled. Therefore, this study found that higher particle concentrations (…) c=1.0-1.5% ) and a higher oil phase volume fraction ( =70-75% It can form emulsion gels with good stability and strength.
[0085] Table 1 shows the particle concentration (c) and oil phase volume fraction (c). The effect of oil phase concentration (c = 0.5-1.5%) on Pickering emulsion particle size was investigated. When the oil phase volume fraction was 70%, the Pickering emulsion particle size decreased with increasing particle concentration (c = 0.5-1.5%), with D50 decreasing from 45.45 μm to 11.94 μm. Simultaneously, when the particle concentration was 1.0%, the Pickering emulsion particle size decreased with increasing oil phase volume fraction (c = 0.5-1.5%). As the value increases (=65-75%), D50 gradually increases from 17.64 μm to 20.98 μm.
[0086] Table 1
[0087] like Figure 11 As shown, the Pickering emulsion gel strength gradually increases with increasing particle concentration, reaching a peak at c=1.5% (28.11 g). The Pickering emulsion gel strength also gradually increases with increasing oil phase volume fraction. It reaches its peak value (19.95g) at 75%.
[0088] Using sunflower seed oil as a control, the lutein-protecting ability of Pickering emulsions with different particle concentrations and oil phase volume fractions under ultraviolet irradiation was compared. Figure 12 As shown, under ultraviolet light irradiation, the lutein retention rate of pure sunflower seed oil decreased very rapidly, dropping significantly on day 1 and almost to zero by around day 4. In contrast, all sample emulsions still exhibited high lutein retention rates on day 7, indicating that the Pickering emulsion stabilized by MQP-ASKG composite particles has a strong lutein protection capacity. Figure 12 As shown in Figure A, the lutein retention rate gradually increased with increasing particle concentration. On day 7 of storage, the lutein retention rate at a particle concentration of 1.5% (87%) was significantly higher than that at a particle concentration of 0.5% (66%). This indicates that increasing the particle concentration helps improve the stability of lutein in Pickering emulsions and slows down lutein loss. The images showing different oil phase volume fractions (…) Figure 12 (B) It can be observed that the oil phase volume fraction has a relatively small effect on lutein retention. Throughout the storage period, the lutein retention rates at 70% and 75% oil phase volume fractions were quite similar, and slightly higher than those at 65% oil phase volume fraction, but the difference was not significant.
[0089] Based on the above results, in Example 2, the composite particles with a MQP:ASKG ratio of 1:1 had the smallest particle size, the largest absolute value of zeta potential, and a three-phase contact angle of 109.71 ± 0.70°, demonstrating the ability to stabilize Pickering emulsions; c = 1.5%, At a concentration of 70%, the emulsion exhibited the smallest droplet size (D50 = 11.94 μm), the highest gel strength (28.11 g), the highest centrifugal stability (98.14%), and the best rheological properties. In the comparative examples, other composite ratios (2:1, 3:1, 4:1, 5:1, 1:2, 1:3, 1:4) all had absolute zeta potential values lower than 1:1; at low particle concentrations (c = 0.5%, 1.0%), the emulsion particle size increased, while gel strength and centrifugal stability decreased; at low oil phase volume fractions ( When the oil phase volume fraction (=65%), the emulsion stability decreases significantly, and the high oil phase volume fraction ( When the concentration of MQP:ASKG reaches 75%, the emulsion particle size increases. Therefore, the optimal composite ratio is determined to be MQP:ASKG = 1:1, with c = 1.5%. =70% is the optimal emulsion preparation condition, which will be used in subsequent examples.
[0090] Example 3 This embodiment provides a method for preparing low-fat emulsified sausage, comprising the following steps: According to formula T3 in Table 2, after removing fat and connective tissue from fresh pork back, weigh 200g and place it in a meat chopper. Simultaneously add 20g of pork fat, 20g of MQP-ASKG composite granule-stabilized Pickering emulsion, 40g of ice water, 4g of salt, 0.4g of white pepper powder, and 0.6g of sodium polyphosphate. Chop at 1500 rpm for 30 seconds, repeat twice, and finally chop at 3000 rpm for 1 minute to obtain minced pork. Weigh 50g of minced pork and steam in an 80℃ water bath for 20 minutes to obtain emulsified sausage. After cooling to room temperature, store at 4℃.
[0091] Table 2 Comparative Example 3-1 The difference between this comparative example and Example 3 is that the ingredients are added according to the T1 formula (0% substitution) in Table 2, while the remaining process parameters and operating conditions are the same as in Example 3.
[0092] Comparative Example 3-2 The difference between this comparative example and Example 3 is that the ingredients are added according to the T2 formula (25% substitution) in Table 2, while the remaining process parameters and operating conditions are the same as in Example 3.
[0093] Comparative Example 3-3 The difference between this comparative example and Example 3 is that the ingredients are added according to the T4 formula (75% substitution) in Table 2, while the remaining process parameters and operating conditions are the same as in Example 3.
[0094] Comparative Examples 3-4 The difference between this comparative example and Example 3 is that the ingredients are added according to the T5 formula (100% substitution) in Table 2, while the other process parameters and operating conditions are the same as in Example 3.
[0095] Example 3 and Comparative Examples 3-1 to 3-4 were characterized according to the aforementioned detection method.
[0096] The effect of different proportions of fat replacement with pickering emulsion on the cooking yield of low-fat emulsified sausage, such as Figure 13 As shown, as the proportion of Pickering emulsion replacing fat increased from 25% (T2) to 100% (T5), the cooking yield of low-fat emulsified sausage significantly increased from 95.27%. P<0.05 The yield of the emulsified sausage with Pickering emulsion replacing 100% fat increased by 4.33% compared to the control group T1 (94.25%). This indicates that the Pickering emulsion, which is stabilized by MQP-ASKG composite particles, reduces the water loss of the emulsified sausage during cooking and has better water retention performance.
[0097] The effect of different fat substitution ratios in pickering emulsions on the water retention of low-fat emulsions in the intestines, such as Figure 14 As shown, with the increase in the proportion of Pickering emulsion replacing fat, the water retention of low-fat emulsified intestines gradually increases. P<0.05 The T5 group reached the maximum value (86.77%). The high water retention of low-fat emulsified sausage can improve the cooking yield, which is consistent with the cooking yield results.
[0098] Table 3 shows that, compared with the control group (T1), when the proportion of fat replacement by Pickering emulsion was less than 50%, there was no significant difference in the firmness and chewiness of the low-fat emulsified sausage (P>0.05). However, when the fat replacement ratio was greater than 50%, the firmness and chewiness of the low-fat emulsified sausage were significantly reduced (P<0.05). There was no significant difference in elasticity among all samples (P>0.05). The low-fat emulsified sausage using Pickering emulsion to replace 50% of the fat showed the most similar textural properties to the control group, with no significant differences in firmness, elasticity, cohesion, resilience, and chewiness.
[0099] Table 3 like Figure 15 As shown, compared with the control group (1451.05g), the gel strength of low-fat emulsified intestines first increased and then decreased with the increase of the proportion of fat replaced by Pickering emulsion (P<0.05). When the replacement ratio was 50%, the gel strength reached its peak (1604.46g).
[0100] Figure 16This study demonstrates the effect of Pickering emulsion replacing different proportions of fat on water distribution and migration in low-fat emulsified intestines. Figure 16 As shown in Figure A, all samples exhibited three characteristic peaks, representing bound water tightly bound to macromolecules (0-10 ms, T2b), immobile water located in the gel network structure (10-200 ms, T21), and free water in the interstitial spaces of the myofibril network (200-1000 ms, T22), respectively. P2b, P21, and P22 represent the corresponding peak area percentages
[186] . Compared to the control group (T1), the T2b, T21, and T22 positions of Pickering emulsions replacing different proportions of fat-emulsified intestines shifted to lower relaxation times. Figure 16 B. Figure 16 As shown in Figure C, with the increase of the proportion of Pickering emulsion replacing fat, the T2 relaxation time of low-fat emulsified intestines showed a trend of first decreasing and then increasing (P<0.05), with the T2b (0.24ms), T21 (42.31ms), and T22 (404.73ms) being the smallest in the T3 (50%) group. Compared with the control group (T1), with the increase of the proportion of Pickering emulsion replacing fat, there was no significant difference in bound water (P2b) (P>0.05), while the amount of non-flowing water (P21) first increased and then decreased (P<0.05), and the amount of free water (P22) first decreased and then increased (P<0.05), with the largest P21 (96.16%) and the smallest P22 (2.19%) in the T3 (50%) group.
[0101] like Figure 17 As shown, the low-fat emulsified sausage with a 50% fat replacement ratio of Pickering emulsion showed the highest scores in color (7.6), texture (7.1), juiciness (7.5), mouthfeel (7.4), and overall acceptability (7.4) (P<0.05).
[0102] Based on the above results, the low-fat emulsified sausage with Pickering emulsion replacing 50% of the fat in Example 3 exhibits superior textural properties, gel strength, storage modulus (G'), and sensory quality. It shows a reduction in α-helices and random coils, an increase in β-sheets and β-turns, and a higher proportion of non-flowing water, resulting in a denser, more uniform gel network structure with smaller cavities. In the comparative examples, the 0% replacement group had high fat content and poor oxidative stability, the 25% replacement group showed insufficient lipid-lowering effect, and the 75% and 100% replacement groups exhibited significantly reduced firmness, chewiness, and gel strength. Therefore, replacing 50% of the fat with Pickering emulsion is determined to be the optimal replacement ratio.
[0103] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A Pickering emulsion stabilized by plant protein-polysaccharide composite particles, characterized in that, The Pickering emulsion uses plant protein-polysaccharide composite particles as emulsifiers, plant oil as the oil phase, and water as the water phase; the plant protein-polysaccharide composite particles are composed of ultrasonically modified plant protein and plant gum.
2. The Pickering emulsion according to claim 1, characterized in that, The modified plant protein is modified quinoa protein; the plant gum is Artemisia argyi gum.
3. The Pickering emulsion according to claim 2, characterized in that, The mass ratio of the modified quinoa protein to Artemisia argyi gum is 1:4 to 5:
1.
4. The Pickering emulsion according to claim 3, characterized in that, The mass ratio of the modified quinoa protein to Artemisia argyi gum is 1:2 to 2:
1.
5. The Pickering emulsion according to any one of claims 2 to 4, characterized in that, The modified quinoa protein is obtained by treating natural quinoa protein with low-frequency, high-intensity ultrasound.
6. The Pickering emulsion according to claim 5, characterized in that, The ultrasonic power of the low-frequency high-intensity ultrasonic treatment is 200W-600W.
7. The Pickering emulsion according to claim 1, characterized in that, In the Pickering emulsion, the mass concentration of the composite particles is 0.5%-1.5%; the volume fraction of the oil phase is 60%-75%.
8. The Pickering emulsion according to claim 7, characterized in that, The composite particles have a mass concentration of 1.5% and the oil phase has a volume fraction of 70%.
9. A low-fat emulsified sausage, characterized in that, It is prepared from the following raw materials in parts by weight: 200 parts of pig back, 0-30 parts of fat, 10-40 parts of Pickering emulsion as described in any one of claims 1-8, 40 parts of ice water, 4 parts of salt, 0.4 parts of white pepper powder, and 0.6 parts of sodium polyphosphate.
10. A low-fat emulsified sausage according to claim 9, characterized in that, The Pickering emulsion replaces 50% of the fat.
